Fatigue Status in Relation to Lifestyle in Healthy Japanese Adolescents - Ning Zou; Masaru Kubota; Eriko Kuruma; Chiaki Kojima; Ayako Nagai (International Journal of Pediatrics)
In order to investigate the prevalence of physical, mental, and chronic fatigue syndrome-(CFS-) related fatigue and its relation to lifestyle, 1,225 adolescents (591 males, 634 females) aged 11 to 16 years were asked to complete a self-reported questionnaire on fatigue status and lifestyle in the past one month. There was no gender difference in physical and mental fatigue scores, but CFS-related scores were significantly higher in females than in males. These scores were found to increase with the increase of age. After adjusting for age and gender, multiple regression analysis showed that physical and mental fatigue scores were associated with sleeping hours, extracurricular sports activity, food balance, the frequencies of snacks between regular meals, intake of sugar-sweetened beverages, and visits to the nurse's room. This paper is the first large cross-sectional study on fatigue in healthy adolescents in Japan, albeit there were numerous such studies in Western countries.